O léxico no trabalho de tradução intralinguístico e interlinguístico - Barros, Maria Betânia Arantes (2024)
The National Curricular Common Base (BNCC), as well as other current documents that deal with teaching guidelines, postulate that when it comes to language teaching, we should not be so concerned with grammatical categorizations and classifications, but with making the student learn to reflect on the language in situations of production and interpretation of texts, having the awareness for its improvement until reaching the analysis of a metalinguistic nature. In view of this, we aim to explore the lexical refinement of students, learners of Portuguese as their mother tongue and foreign language, as well as second language learners, showing that the way to the apprehension of a new language is not through the attempt to translate language-language, but yes within the scope of intra/interlinguistic language. Our work consists of identifying linguistic occurrences, present in students' textual productions, which are characterized by lexical inaccuracies, which we will call displacements. Such occurrences will be references for the activity that we intend to develop in teaching based on the theoretical-methodological assumptions of Antonie Culioli's Theory of Predicative and Enunciative Operations (TOPE), which defends meaning as a dynamic process, and not carried out through values. presets.